The transatlantic bloc of states and the political economy of the Transatlantic Trade and Investment Partnership (TTIP). (1st April 2015) - ,
Abstract : The world space is politically built, on the one hand, dominated by large, highly concentrated, capital, with finance standing at the apex and, on the other hand, fragmented along national lines. The contemporary political economy of globalisation is the product of uneven and combined development under the domination of developed countries, defined here as the ''hierarchical transatlantic bloc of states''. At its centre can be found the USA, supported by its long-standing political and military allies in Europe and Asia. The main objectives of the Transatlantic Trade and Investment Partnership (TTIP), analysed in this article, are to facilitate the expansion of its members' share of profits derived from labour and from the ''marketisation'' of nature and the ''commons''; to organise competition between national ruling classes and different states of the transatlantic area at the international level; and to preserve their domination through the enforcement of international rules. The article concludes that, given the strong opposition from ''those from below'' (including trade unions and non-governmental organisations) and the persistent divergences between the negotiating sides, the TTIP should be regarded not so much as a ''turnkey'' project to be easily wrapped but as a work in progress by the USA and the European Union (EU), constituting an overarching forum that will cement the transatlantic bloc in order to promote the broad interests of the huge concentration of capital based on their territories.